Inversion Geochemistry as a Method for Interpreting Source Rock Criteria of Oil Samples: A Case Study from the Bobonaro Area, Maliana Basin, Timor-Leste - Pires, Joanico; Subroto, Eddy Ariyono; Kesumajana, Asep Heri Patria (UIR PRESS, 2024)
In general condition, crude oil samples are difficult to obtain. However, when the crude oil samples are obtained, researchers will be able to estimate the possibility of their source rock, as long as the samples are analyzed in sufficient detail. In this study, the samples used as case studies are the Pualaka and Suai Loro oil seepage samples from Bobonaro area, Maliana Basin, Timor Leste. The petroleum samples obtained happened to be in relatively fresh condition. The analysis carried out included analysis using GC and GC-MS with the objects of analysis being biomarkers, i.e. triterpane compounds with m/z 191 and steranes with m/z 217. The results obtained showed that the two seepage oils were suspected to belong to one oil family whose source rock was estimated to be deposited in a marginal marine area with a dominant algae supply and few higher plants with Pre-Tertiary geological age. The maturity of the two petroleum samples was relatively high, at the stage of peak oil generation. By knowing such characters, researchers will be able to predict sedimentary rocks in the basin area that are of the same type as petroleum characters using inversion geochemistry technique. The most possible source rock of the crude oils is the Babulu Formation.